Enhanced Recovery of Cellulose from Corncob Biomass by Binary Acids Pretreatments for Improved Bioethanol Production - Adane, Asefa (ASTU, 2021)
Pretreatment Is A Pre - Requisite Step In Bioethanol Production From Ligno cellulosic Biomass. It Required To Remove Hemi cellulose And Lignin, Increasing Cellulose Recovery And The Porosity Of The Substrate For Saccharification. In The Present Study, Chemical Pretreatment Of Corncob Was Performed Using New Approach Techinque Binary Acids (H2so4 + Ch3cooh) In Different Ratios. Among All The Investigated Binary Acids Ratios, The Pretreatment With (1:1) Ratio Removed Maximum Hemicellulose (42.02%) And Lignin (35.8%) With The Cellulose Recovery Of 43.5%. After Optimizing Different Operating Conditions Such As Binary Acids Concentration, Biomass Loading Ratio, Pretreatment Temperature, And Time Using Design Expert Software For (1:1) Binary Acids Ratio, The Removal And Recovery Have Been Increased. The Attained Maximum Removal Of Lignin And Hemicellulose Were 81.41??2.3% And 85.6??1.8%, Respectively, With Enhanced Cellulose Recovery Of 93.5??1.3% At The Optimum Conditions Of Binary Acids Concentration (3%, V/V), Biomass Loading Ratio (0.1 G/Ml), Pretreatment Temperature (120 Oc) And Time (60 Min). The Obtained Pretreatment Data Were Statistically Analyzed Using One-Way Anova And Validated Experimentally. The Sem, Ftir And Xrd Analysis Were Used To Characterize The Raw Corncob, Binary Acids Pretreated Corncob, Recovered Cellulose And Micro-Cellulose (Commercial Grade) At Different Processing Stages. The Sem And Ftir Spectra Revealed The Removal Of Hemicelluloses And Lignin From The Corncob Biomass By Binary Acids Pretreatment. The Xrd Results Also Confirmed A Change In The Crystallinity Index Of Corncob Biomass. Subsequently, Dilute Sulfuric Acid Hydrolysis Of Recovered Corncob Cellulose Was Investigated Under Various Acid Concentrations, Temperatures And Residence Times. The Maximum Glucose Concentration Attained Was 55.4 Mg/Ml At 120 Oc With An Acid Concentration Of 3% (V/V) For 45 Min Of Hydrolysis Time. Ethanolic Fermentation Was Carried Out At 30 Oc With 200 Rpm For 4 Days With The Recovered Glucose Using Saccharomyces Cerevisiae. The Maximum Bioethanol Concentration 24.6 Mg/Ml Was Attained. The Characterization Of Produced Ethanol Was Done By Ftir, Which Confirmed The Functional Groups Of Ethanol Such As O-H, C-O, -Ch2 And Ch3. This Study Demonstrates That Binary Acids Pretreatment Is An Alternative And New Approach For The Pretreatment Of Lignocellulosic Biomass. The Optimized Process Conditions Could Also Successfully Increase The Cellulose Recovery, Improve Fermentable Sugar And Bioethanol Yield.
Keywords: Corncob pretreatment; Binary acids; Enhanced cellulose recovery; Hydrolysis; Fermentation